Carbonation treatment of recycled concrete aggregate

Carbonating recycled concrete aggregates with CO2 improves mechanical properties and reduces environmental hazards, addressing the limitations of RCA in construction applications.

JP2025503292APending Publication Date: 2025-01-30NUTECH VENTURES LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024545208
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-28
Filing Date
2023-01-27
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

The mechanical characteristics of recycled concrete aggregates (RCA) are inferior to natural aggregates due to past abuse, and their use is limited by environmental concerns such as high alkalinity and heavy metal contamination, which can damage groundwater quality.

Method used

A method involving the carbonation of RCA using carbon dioxide (CO2) in a controlled environment to alter mineral compositions, improving mechanical properties and reducing environmental hazards.

Benefits of technology

The carbonation process enhances the mechanical strength and durability of RCA, making it suitable for replacing natural aggregates while significantly reducing pH and heavy metal concentrations, thus minimizing environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503292000001_ABST
    Figure 2025503292000001_ABST
Patent Text Reader

Abstract

A method for processing recycled concrete aggregate (RCA), comprising constructing a chamber configured to form an airtight seal, loading the RCA into the chamber, hermetically sealing the chamber, pressurizing the chamber with carbon dioxide gas, monitoring the pressure and humidity in the chamber, and controlling the pressure and humidity until predetermined conditions are met.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This patent application claims the benefit of U.S. Provisional Patent Application No. 63 / 304,184, filed January 28, 2022, which is incorporated by reference in its entirety for all purposes. [Background technology]

[0002] As infrastructure construction and renovation continues, the demand for sand, gravel, rock, and concrete has increased dramatically, consuming enormous amounts of natural resources each year. For example, the annual demand for aggregates in the United States is 1.8 billion tons (1.6 x 10 12 It is estimated that the total amount of waste concrete generated in construction and demolition works exceeds 100 kg per year. Moreover, huge amounts of construction and demolition (C&D) waste are generated every year, especially waste concrete. Concrete accounts for approximately 70% of the total demolition waste. Meanwhile, landfill costs are constantly increasing. In this light, recycling and reuse of waste concrete can significantly help address these challenges.

[0003] One of the most promising approaches to reuse such waste concrete may be to produce recycled concrete aggregate (RCA) by crushing and sieving. RCA is a popular substitute for natural stone aggregates used in parking lots, backfill, home landscaping, etc. However, the mechanical properties of RCA may be inferior to those of natural aggregates due to the large amount of residual paste and previous abuses including weathering. Furthermore, there are potential environmental concerns for the use of RCA due to the potential for contamination by heavy metal leachate and high pH. For example, one research group demonstrated high alkalinity and high heavy metal concentrations in RCA leachate through laboratory and field testing. This issue has greatly limited the effective use of RCA in state or local agencies. Furthermore, RCA may impair groundwater quality. Thus, there is a critical need to develop a means to improve the mechanical properties of RCA while addressing the environmental concerns for its use. Summary of the Invention

[0004] One or more aspects of the present disclosure provide a method for processing recycled concrete aggregate (RCA), the method including constructing a chamber configured to form an airtight seal; loading the RCA into the chamber; hermetically sealing the chamber; pressurizing the chamber with carbon dioxide gas; monitoring pressure and humidity in the chamber; and controlling the pressure and humidity until predetermined conditions are met.

[0005] One or more aspects of the present disclosure provide a treated recycled concrete aggregate (RCA), comprising: the RCA loaded and hermetically sealed in a chamber; and treating the RCA by exposing it to a carbon dioxide enriched atmosphere under elevated pressure in the chamber, wherein the temperature and humidity of the atmosphere are monitored and controlled until predetermined conditions are met, wherein treating the RCA changes the proportions of constituent minerals in the RCA, increasing the proportions of calcium carbonate and silica as a result of the reaction of calcium hydroxide, calcium silicate hydrate and carbon dioxide.

[0006] One or more aspects of the present disclosure provide a method of carbonating recycled concrete aggregate (RCA), the method including constructing a chamber configured to form an airtight seal, loading the RCA into the chamber, hermetically sealing the chamber, pressurizing the chamber with carbon dioxide gas, monitoring the pressure, temperature, and humidity in the chamber, and controlling the pressure, temperature, and humidity until predetermined conditions are met.

[0007] One or more aspects of the present disclosure provide a system for processing recycled concrete aggregate (RCA). The system includes a chamber configured to form an airtight enclosure and having a volume between 10 L and 3×10 4the chamber including a door configured to form an airtight seal at L; at least one dehumidifier disposed within the chamber and configured to maintain humidity within the chamber; at least one system disposed within the chamber and configured to collect water from the at least one dehumidifier; at least one blower disposed within the chamber and configured to circulate CO2 gas and moisture within the chamber; at least one heating element; at least one pressure sensor disposed within the chamber and configured to measure pressure within the chamber; at least one humidity / temperature sensor disposed within the chamber and configured to measure humidity and temperature within the chamber; a supply of carbon dioxide gas operably connected to the chamber via an inlet valve; and an outlet valve disposed on the chamber and configured to exhaust gas from the chamber. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 shows a chamber for carbonation of RCA in one or more embodiments. [Figure 2A-2B] 2A and 2B show two laboratory chambers for carbonation of RCA according to one or more embodiments. [Diagram 3] FIG. 3 shows a closed bucket for leaching testing in one or more embodiments. [Figure 4] FIG. 4 illustrates a sample identification system according to one or more embodiments. [Diagram 5] FIG. 5 shows a bar graph of all measured aggregate crushing values ​​in one or more embodiments. [Figure 6A-6B] 6A and 6B show bar graphs of LA wear mass loss according to one or more embodiments. [Figure 7] FIG. 7 shows a bar graph of LA wear mass loss in accordance with one or more embodiments. [Figure 8A-8B] 8A and 8B show bar graphs of freeze-thaw mass loss in accordance with one or more embodiments. [Figure 9] FIG. 9 shows a bar graph of freeze-thaw mass loss in one or more embodiments. [Figure 10]FIG. 10 illustrates a bar graph of compressive strength of concrete samples according to one or more embodiments. [Figure 11] FIG. 11 illustrates a bar graph of fracture modulus of concrete samples according to one or more embodiments. [Figure 12] FIG. 12 illustrates a bar graph of plastic modulus and Poisson's ratio of concrete samples according to one or more embodiments. [Figure 13] FIG. 13 shows a bar graph of surface resistivity and bulk resistivity of concrete samples according to one or more embodiments. [Figure 14A-14B] 14A and 14B show plots of carbon dioxide mass per RCA mass as a function of time at various pressures, according to one or more embodiments. [Figure 15] FIG. 15 shows a plot of carbon dioxide mass per RCA mass as a function of time at various pressures in accordance with one or more embodiments. [Figure 16A-16B] 16A and 16B show plots of mass carbon dioxide consumption and mass carbon dioxide per mass RCA as a function of time at various pressures, according to one or more embodiments. [Figure 17A-17B] 17A and 17B show plots of mass carbon dioxide consumption and mass carbon dioxide per mass RCA as a function of time at various pressures, according to one or more embodiments. [Figure 18A-18B] 18A and 18B show plots of mass carbon dioxide consumption and mass carbon dioxide per mass RCA as a function of time at various humidities, according to one or more embodiments. [Figure 19A-19B] 19A and 19B show plots of mass carbon dioxide consumption and mass carbon dioxide per mass RCA as a function of time at various temperatures, according to one or more embodiments. [Figure 20A-20B] 20A and 20B show plots of mass carbon dioxide consumption and mass carbon dioxide per mass RCA as a function of time at various humidities, according to one or more embodiments. [Figure 21A-21B]21A and 21B show plots of mass carbon dioxide consumption and mass carbon dioxide per mass RCA as a function of time for various sample preparations, in accordance with one or more embodiments. [Figure 22] FIG. 22 is a flow chart of a method for processing recycled concrete aggregate, according to one or more embodiments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Detailed Description Applicants have investigated improving the mechanical and chemical properties of old concrete aggregates through the introduction of carbon dioxide (CO2). Experiments were conducted in a laboratory setting using a medium-sized prototype chamber that was developed for the experiment and tested for suitability therefor. The chamber was constructed to process approximately one tonne (910 kg) of loose volume of resource-controlled RCA, although the chamber, system, method and generated products disclosed herein are not intended to require resource-controlled RCA. After approximately 40 tests using the prototype chamber and approximately 30 tests in the laboratory, Applicants have demonstrated the effectiveness of aggregate improvement through carbon dioxide treatment.

[0010] Treatment of RCA with carbon dioxide (CO2) changes the proportions of constituent minerals in the RCA, increasing the proportions of calcium carbonate (CaCO3) and silica (SiO2) as a result of the reaction of calcium hydroxide (Ca(OH)2), calcium silicate hydrate (CSH) and carbon dioxide (CO2).

[0011] The long-term impact of this research is potentially enormous. The disclosure could have a positive environmental impact on the $19 billion stone aggregate industry. By upgrading RCA for high-value uses, the treated RCA described herein could be diverted from landfills (end-of-life concrete is the largest landfill by volume in the United States). The treated RCA is sustainable, and the disclosed method could provide substantial carbon sequestration. The use of RCA as a replacement for virgin material could extend the life of quarries and reduce pressure on natural habitats. Additionally, the reduction of pH and heavy metals in RCA leachates could protect groundwater.

[0012] One of the most promising approaches to reuse such waste concrete may be to produce recycled concrete aggregate (RCA) by crushing and sieving. RCA is a popular substitute for natural stone aggregate for parking lots, backfill, home landscaping, etc. However, the mechanical properties of RCA may be inferior to those of natural aggregates due to the large amount of residual paste and previous abuses including weathering. Furthermore, there may be environmental concerns for the use of RCA due to the possibility of contamination by heavy metal leachate and high pH. For example, one research group showed high alkalinity and high heavy metal concentrations in RCA leachate through laboratory and field testing. This issue has greatly limited the effective use of RCA in state or local agencies. Furthermore, RCA may impair groundwater quality. Thus, there is a critical need to develop a means to improve the mechanical properties of RCA while addressing the environmental concerns for its use.

[0013] Laboratory studies A total of 27 separate laboratory-scale carbon dioxide treatments were conducted using two treatment chambers with volumes of 10 L and 30 L. In particular, the effects of key variables, including carbon dioxide supply pressure, humidity (RH), treatment temperature, initial gas conditioning (CO2 vacuum vs. CO2 purge) and sample preconditioning method, on carbon dioxide consumption for the treatment of RCA were thoroughly investigated. Mechanical and pH test results confirmed that RCA samples were properly carbonated with carbon dioxide. Calculated carbon dioxide mass consumption reveals that consumption increases with initial carbon dioxide supply pressure, exposure time and temperature. Moreover, test results suggest that the optimal RH to achieve maximum carbon dioxide consumption may be 50±10%, especially 50±5%. It was observed that the mechanical improvement of RCA was more pronounced in the treatment chamber with larger volume (30 L) because more carbon dioxide was supplied.

[0014] Commercial-scale prototyping Capacity is 500 gallons (1.9m 3 A mid-sized carbon dioxide processing chamber 100 of 1.0 m2 was constructed as a commercial-scale prototype. The prototype chamber 100 had a length (L) of 116 inches and a height (H) of 38.5 inches. A commercial chamber may have a volume of 1000 cubic feet (28,000 L) or more. As an example, a commercial chamber may have a diameter (or height) of 8 feet and a length of 20 feet. The chamber 100 is equipped with a pressure sensor 116 and a humidity / temperature (RH / T) 118 sensor, gas inlet 124 and outlet 126 valves, rails to accommodate the RCA basket, a water collection vessel 114, a blower 122, and a dehumidification system 112. The dehumidification system can be a conventional dehumidifier, a desiccant-type dehumidifier, or other suitable system. The chamber door 102 is designed to be airtight to facilitate loading and unloading of the RCAs and also to prevent carbon dioxide leakage during RCA processing.

[0015] Carbon dioxide treatment of RCA using prototypes A total of 35 separate carbon dioxide treatments of RCA were conducted using prototypes at various conditions. Conditions tested included carbon dioxide pressure, carbon dioxide supply conditions, RCA loading arrangement (simple loose loading vs. separate loading into baskets ensuring good contact with CO), RCA volume, treatment time, temperature, and initial moisture content of the RCA to elucidate the effect of each variable on the carbon dioxide consumption and resulting mechanical and environmental improvements of the carbon dioxide-treated RCA.

[0016] Conditions tested included carbon dioxide pressures: 1, 5, 10, 20, 40, and 60 pounds per square inch gauge (psig, 6.9, 34.5, 68.9, 138, 276, and 414 kPa, respectively); carbon dioxide supply: initial pressure vs. continuous carbon dioxide supply; loading arrangement: in basket vs. simple loose loading; RCA volume: 10% vs. 20% of internal chamber volume; treatment time: 1 hour to 24 hours; and initial moisture content of the RCA: normal drying vs. with additional drying. Higher pressures (e.g., 80 psig or greater) are desirable. Additional tests were performed at 80 psig (552 kPa) until failure of the chamber to seal. A wide range of carbon dioxide mass consumption and mechanical-environmental test results were obtained using various variables. Analysis of the test results reveals the most effective and optimal parameter ranges.

[0017] Mechanical and environmental testing of carbon dioxide treated RCA using prototypes. Five different mechanical and two environmentally relevant tests were conducted using prototype and CO2-treated RCA. In particular, 22 separate tests of specific gravity and absorbency, 117 individual tests of Aggregate Crushing Value (ACV) index, 23 tests of Los Angeles (LA) abrasion resistance and 23 tests of freeze-thaw (FT) resistance were conducted on the CO2-treated RCA using the fabricated prototypes. In addition, 36 individual phenolphthalein tests and over 150 leachate tests were conducted to investigate pH and heavy metal concentrations in the leachate of the CO2-treated RCA.

[0018] The mechanical properties show a wide range of improvements: ACV improvement up to about 20%, LA abrasion mass loss improvement up to about 16%, and FT mass loss improvement up to about 59%. All the CO2 treated RCAs were observed to meet the requirements for replacing natural aggregates (i.e., less than 40% and 45% mass loss due to abrasion of concrete and subgrade per AASHTO T96 and NDOT Specification 1033.02, respectively). Subgrade refers to a rocky substrate of perhaps 4-6 inches (10-15 cm) for water runoff. Moreover, concrete specimens mixed with CO2 treated RCAs meet the requirements for replacing natural aggregates in terms of minimum strength (psi) of 3,500 pounds per square inch (24 megapascals (MPa), minimum modulus of rupture of 600 psi (4 MPa), and FT resistance.

[0019] Regarding the environmental aspects, after 24 hours of exposure to various carbon dioxide treatment conditions, the pH of the leachate was reduced by up to 2 pH units, while the concentration of heavy metals was reduced by more than 50%, compared to that of the prototype RCA. Notably, most of the heavy metal concentration levels in the collected leachate were well below the EPA's Maximum Contaminant Levels (MCLs) for drinking water.

[0020] All small and medium scale carbon dioxide processing data as well as mechanical and environmental test results were compiled and analyzed in detail. Below, the results for each variable are listed first, followed by the ranges of the variables in combination.

[0021] Carbon dioxide pressureA wide range of carbon dioxide pressures was studied, from 1 psig to 60 psig (6.9 kPa to 410 kPa) gauge pressure. The test results indicated that carbon dioxide consumption was faster at higher carbon dioxide pressures. The ACV test results did not show a strong correlation between strength gain and CO2 pressure. The ACV index may be more related to the bulk properties of the RCA. The mass loss after LA abrasion and FT resistance tests showed very good correlation with carbon dioxide pressure and therefore carbon dioxide consumption. The pH of the leachate was also further reduced at higher carbon dioxide pressures due to RCA treatment. Finally, the concentrations of heavy metals did not show a strong correlation with carbon dioxide pressure. However, all of the heavy metal concentrations remained well below the EPA's maximum contaminant levels (MCLs) for drinking water. Among the test results, FT mass loss showed the strongest correlation with CO2 consumption, with a P value of about 0.035 from the regression analysis. This is a noteworthy result, as FT mass loss is one of the most important indicators of aggregate durability. Higher CO2 pressure could induce faster carbonation of RCA with higher penetration into the aggregate interior. Furthermore, the test results suggest that the proposed treatment method is most effective for improving the surface-level mechanical properties of RCA.

[0022] Processing time : Various treatment times from 1 hour to 24 hours were examined. From the results of carbon dioxide consumption from medium-scale and laboratory-scale tests, it was observed that the treatment time could be divided into three zones: 0-6 hours: fastest rate of carbon dioxide treatment of RCA, 6-12 hours: moderate rate, and 12-24 hours: slow rate of treatment. Therefore, the most effective time of treatment could be within 12 hours, especially the first 6 hours. The mass loss of LA abrasion and FT resistance tests showed a good relationship with the treatment time. Regression analysis shows that all mechanical tests - ACV, LA abrasion and FT resistance - are statistically highly dependent on the treatment time (P values ​​are approximately 0.003, 0.040 and 0.0001, respectively). Overall, the treatment time could be another important factor that can significantly affect the carbon dioxide treatment.

[0023] RCA massTwo different RCA masses, 10% and 20% of the total volume of the treatment chamber (i.e., approximately 260 kg (570 pounds (lb)) and 730 kg (1610 lb), respectively), were evaluated using a mid-scale prototype. Two different RCA masses, in amounts of 1.2 kg and 5 kg, were also tested in the laboratory-scale treatment chamber. In theory, a higher mass (volume) of RCA can reduce the volume that the carbon dioxide can occupy, reducing the contact between the RCA and the carbon dioxide inside the chamber. The main finding here is that the airflow of carbon dioxide between the aggregates is important.

[0024] humidity : The effect of RH on carbon dioxide consumption, mass gain of RCA and ACV was thoroughly examined using a laboratory-scale treatment chamber (30 L). A wide range of RH levels (approximately 2% to approximately 80%) was tested. Data analysis suggests that maximum carbon dioxide consumption may be achieved at a RH of 50% to 55%. Mass gain of RCA after carbon dioxide treatment also showed a higher increase for a RH of 50±5%. ACV index did not show a strong correlation, but generally, ACV index showed the highest improvement at a RH of 50% to 55%. In this regard, the optimal RH may be 50±5%.

[0025] Processing temperature : The effect of treatment temperature within a limited range was mainly studied in the laboratory. Test results pointed to an improvement in carbon dioxide consumption at higher temperatures. The mass increase of RCA after carbon dioxide treatment also showed a higher percentage increase at higher treatment temperatures, whereas the ACV index did not show a strong dependence on treatment temperature. From a geochemical point of view, the treatment temperature may play an important role by accelerating / decelerating chemical reactions.

[0026] Preconditioning (initial moisture content as a percentage of mass): Preconditioning for the medium-scale treatments was kept similar (3-5%) for all tests. Despite such a narrow range of initial moisture content (i.e. moisture content before entering the chamber), FT resistance showed a good correlation with it (P value = 0.0016) from regression analysis. That is, FT resistance tests resulted in less mass loss at lower initial moisture contents. Theoretically, the initial moisture content could play an important role in the carbonation process. That is, moisture may be necessary to initiate the chemical reaction, but high moisture content may hinder the penetration of carbon dioxide into the RCA and thus carbonation. In this respect, preconditioning RCA at optimal moisture level could be another important factor.

[0027] Based on the observation of all test variables, the optimal ranges for the test variables can be summarized in Table 1.

[0028] [Table 1]

[0029] Fabrication of carbon dioxide treatment chamber A prototype chamber 100 was constructed using a 500 gallon (1900 L) propane tank (see FIG. 1). The tank was modified to have a door 102 with six screw-on tailgate latches that hold the outward swinging door 102 closed during processing. To obtain an airtight seal, a flat 2×0.25 inch (5.0×0.64 cm) steel lip was welded to the body of the tank and an additional lip and latch support was welded to the door. A natural rubber seal was placed on top of the 2 inch lip, glued in place, and then sealed with a rubber gasket sealant. The bottom of the tank was widened for additional stability during processing and to support the additional weight of the new door. A wider bottom stand 104 was constructed using 4×2 inch (10×5 cm) square steel tubing. The processing basket 106 was constructed from expanded metal, angle iron, and flat steel bar. In one or more embodiments, the processing basket may be 26 inches in length. A total of six wheeled baskets 106 were fabricated to hold the lock during processing. Wheels 108 were added to the baskets to allow them to roll onto welded rails 110 in the processing chamber 100. In addition to the basket 106 and general tank modifications, a stand for the dehumidifier 112 was installed on the chamber door 102, and a metal box (water collection vessel 114) was fabricated to contain the water collected by the dehumidifier 112 during processing. Carbon dioxide intake ports, sensor ports, pressure relief valves (or blow-off valves), and openings for electrical components were fabricated to complete the chamber 100. After completing the modifications to the new processing chamber design, the chamber 100 was tested to hold a maximum gauge pressure of 65 psig (450 kPa) (note that pressure in this disclosure is gauge pressure unless otherwise indicated). In later tests, the rubber chamber failed to seal at 70 psig (480 kPa).

[0030] Recycled concrete aggregates: origin and preparation The material used in the experiment was a mixed blend from an airfield and highway. The material was crushed using two crushers (McCloskey J50 jaw crusher and McCloskey I44 impact crusher) and then screened using a McCloskey S190 screener station to have a nominal maximum size of 1 inch (2.5 cm) for the aggregate (NMSA) RCA sample.

[0031] Medium-scale carbon dioxide processing The construction and different parts of the mid-sized prototype chamber 100 have been described above. The monitoring and control system includes a dehumidifier 112 (controls the humidity of the chamber during processing), a pressure transducer sensor 116 (Omega, 0-100 psig, i.e. 0-690 kPa), a temperature / humidity sensor 118 (Vaisala, HMP110), a carbon dioxide high purity cylinder 120 (99.9% purity grade, Matheson), and a data acquisition system (Keysight 34972A) that records the pressure and temperature / RH during processing. The experiments used high purity carbon dioxide, but lower purity carbon dioxide, e.g., industrially produced carbon dioxide, can also be used. The prototype chamber 100 is shown in FIG. 1.

[0032] Medium-scale carbon dioxide processing Test procedure The treatment chambers were placed inside the factory to keep the temperature and humidity constant and reduce the effects of sudden temperature / humidity changes with seasons and time. The RCA samples were placed inside the factory, spread on the floor, and dried using an oscillating fan for 24 hours before treatments began. This method may have helped to ensure that the moisture content and temperature of the RCA samples were consistent before carbon dioxide treatments began for all treatments. The RCA samples were periodically turned over using a shovel to facilitate drying.

[0033] Two different loading configurations (basket and simple loose loading) were used to study the effect of loading configuration on RCA treatment. Thus, in the basket loading configuration, six wheeled baskets 106 were loaded equally with pre-dried RCA samples using a shovel and then placed in the chamber 100 in two layers, one layer at a time, as shown in FIG. 1. In the simple loose loading configuration, similar volumes of samples were first measured by loading six baskets, then loaded into the treatment chamber and spread evenly on the bottom of the chamber 100. In this case, a water collection container 114 was placed on top of the samples.

[0034] After the RCA samples were loaded into the treatment chamber 100, the dehumidifier 112 was set to 40% humidity to ensure that the average humidity of the chamber during carbon dioxide treatment was 50-60%. The chamber door 102 was then tightly closed and carbon dioxide was pressurized into the chamber 100 up to 1-2 psig (6.9 kPa-13.8 kPa), and then the pressure was released through the pressure relief valve 126 to purge the air in the chamber 100 to pure carbon dioxide during treatment. The chamber 100 was then pressurized until a desired carbon dioxide pressure was reached, at which point the carbon dioxide intake valve 124 was closed (i.e., CO2 set pressure). As a second carbon dioxide supply mode, the intake valve 124 was left open at a certain level to ensure a continuous supply of carbon dioxide gas to the chamber 100, keeping the chamber pressure at a constant level (i.e., continuous supply of CO2). During treatment, the carbon dioxide pressure, temperature and humidity in the chamber 100 were recorded using sensors 116, 118 connected to the treatment chamber and a data acquisition system and computer. Carbon dioxide treatment was stopped either after all carbon dioxide gas was consumed (carbon dioxide pressure in the chamber reached zero) or after 24 hours if carbon dioxide pressure had not reached zero after 24 hours of treatment.

[0035] RCA Sampling for Laboratory Mechanical and Environmental Testing After the carbon dioxide treatment was completed, the remaining carbon dioxide pressure was released using the pressure relief valve 126 and the chamber door 102 was opened. For each treatment, three buckets (5 gallon (19 L) capacity) were collected and transferred to the laboratory for further mechanical and environmental testing. Due to the importance of sampling and having representative samples, sampling was performed similarly for all treatments. In this regard, the basket placement method filled each sample bucket with two shovelfuls from each basket. For the simple loose loading method, buckets were filled with two shovelfuls from the top, middle and bottom of the RCA pile in the chamber. A total of 35 separate treatments were performed with various conditions as shown in Table 2. For simplicity, each treatment condition is abbreviated as follows: SPB10: Initial setting pressure, basket, 10% volume; SPB20: Initial setting pressure, basket, 20% volume; SPD20: Initial pressure, simple loose loading, 20% volume; CPB20: Continuous pressure, basket, 20% volume.

[0036] [Table 2]

[0037] Lab-scale carbon dioxide treatment Test Setup The laboratory processing setup 200 includes a sealed processing chamber 204 (10 L or 30 L capacity), a pressure transducer 208 (Omega, 0-200 psig (0-1.4 MPa)) and a temperature / humidity sensor 212 (Vaisala, HMP110) connected to the chamber. The sensors 208, 212 are connected to a data acquisition system 216 (Keysight; 34972A) to record the pressure, temperature and RH in the processing chamber 204 during processing. A high purity (99.9%, Matheson) carbon dioxide cylinder 220 is also connected to the processing chamber 204 via a pressure regulator 224 to control the rate of carbon dioxide supply to the processing chamber 204. Each processing chamber 204 has two valves on the top surface for vacuum / pressure relief purposes, one for carbon dioxide inlet 228 and the other for a safety valve 232, as shown in Figures 2A and 2B. The carbon dioxide inlet valve 228 can be a needle valve. The chamber includes racks 236 (eg, two for a 10 L chamber, four for a 30 L chamber) for holding RCA samples 240 and ensuring sufficient surface contact between the RCA and carbon dioxide.

[0038] Test procedure For the laboratory CO2 treatment, specific size RCA samples were used to minimize size effects and to better control the CO2 treatment and analysis. For this, the same RCA from the medium-scale treatment was additionally sieved. Samples that passed the 0.5 inch (1.3 cm) sieve but were retained on the 3 / 8 inch (1.0 cm) sieve were collected for the laboratory CO2 treatment. The sieved RCA samples were first preconditioned to ensure consistent initial RH and temperature (T) of the samples inside the control chamber (with T = 73.4-77°F (24 ± 1°C) and RH = 50% ± 1) for 24 hours before treatment began. A specific amount of Silica Gel 244 (sg; Interra Global) was then placed on the bottom of the chamber (or as an additional layer in the middle of the chamber in case of the 30 L chamber) to control the RH inside the chamber during treatment. Afterwards, a certain amount of preconditioned RCA sample (2.6 pounds (1.2 kg) in the 10 L chamber and 11 pounds (5 kg) in the 30 L chamber) was equally placed on the rack and then moved to the processing chamber 204. The chamber lid was then tightly closed and the carbon dioxide injection tube was also connected to the chamber. To ensure pure carbon dioxide gas in the chamber, a low carbon dioxide pressure (2-3 psig (13.8-20.7 kPa)) was applied, followed by venting the injected CO2 through the pressure relief valve 232 (i.e., CO2 purge). Also, three carbon dioxide injection / vacuum (up to 13 psig (90 kPa)) cycles were applied for processing with the chamber of 10 L volume (i.e., CO2 vacuum). The vacuum pump 248 was used to vent. Carbon dioxide was then injected into the chamber up to a certain pressure level and the valve was closed.

[0039] After 24 hours, the pressure relief valve 232 was opened to release the carbon dioxide gas in the chamber and the chamber lid was opened. The treated RCA was collected from the chamber and the weight of the samples was also measured after treatment. Six individual RCA samples were randomly selected for phenolphthalein testing on the surface and cross-section of the treated samples. The remaining samples were prepared for ACV testing and moisture content measurement. Table 3 summarizes the laboratory-scale carbon dioxide treatment conditions for the two treatment chambers.

[0040] [Table 3]

[0041] Physical and Mechanical Testing To evaluate the physical and mechanical properties of the RCA samples after carbon dioxide treatment, the untreated (pristine) and carbon dioxide treated RCA samples were subjected to the appropriate specifications of physical and mechanical tests as shown in Table 4. The detailed test procedures involved in each laboratory test are as follows:

[0042] [Table 4]

[0043] Specific gravity and absorbency Specific gravity and absorbency tests were performed based on ASTM C127 standard. Due to potential uncertainties of high variability of RCA, all samples were re-sieved to the same grain size (#57 according to ASTM C33) for higher accuracy. Furthermore, due to the high absorbency of RCA, RCA specimens were soaked for 72 hours instead of 24 hours (as suggested by the standard) to ensure full saturation of the RCA samples. The procedure consisted of soaking the RCA sample (at least 6.6 pounds (3 kg)) in water, followed by removing the sample from the water and wrapping it in a large absorbent towel to remove the surface water. The mass of the surface dry saturated (SSD) sample in air is then obtained, followed by measuring the mass of the sample in water to identify the exact volume of the sample. Afterwards, the sample is oven dried at 230±9°F (110±5°C) for 24 hours. The absorbency and specific gravity were then calculated using the following equations:

[0044]

number

[0045]

number

[0046]

number

[0047] where A is the mass of the oven dried test sample in air, B is the mass of the SSD sample in air, and C is the mass of the SSD sample in water.

[0048] Aggregate Crushing Value (ACV) The ACV test was carried out based on the modified BS 110-812 standard. A single size RCA sample (1 / 2 to 3 / 8 in. (1.3 to 1.0 cm)) was placed inside a 6 in. (154 mm) inner diameter steel ring with a maximum height of 2 in. (5 cm) and compacted by tamping 25 times with a 5 / 8 in. (15.9 mm) diameter tamping rod. The load was applied at a rate of 0.35 ± 0.05 in. / min (0.15 ± 0.02 mm / s) until a load of 30,000 kips (133 kN) was reached, followed by immediate load release. The steel ring with the crushed RCA was placed on a vibrating table to vibrate and loosen the compacted RCA sample. The crushed RCA sample was sieved using a No. 8 sieve. The aggregate crush value (ACV) was calculated as the percentage of particles that passed the No. 8 sieve using the following equation:

[0049]

number

[0050] Los Angeles (LA) Wear The LA abrasion test was conducted according to the ASTM C131 standard. Specifically graded samples were prepared by combining 5 lb (2.5 kg) of 0.5 inch (1.3 cm) size RCA and 5 lb (2.5 kg) of 3 / 8 inch (1.0 cm) size RCA. The sample is then placed in the LA tester with a charge of 11 steel balls of 440 g each. The machine is then rotated at a speed of 30-33 revolutions per minute (rpm) for 500 revolutions. After the 500 revolutions are completed, the material is discharged and sieved through a No. 12 sieve. The mass passing through the No. 12 sieve was recorded and the LA abrasion mass loss was calculated using the following equation:

[0051]

number

[0052] Freeze and thaw (FT) resistance The freeze-thaw (FT) resistance of the aggregates was evaluated based on the CSA A23.2-24A standard. Although the standard requires testing of all size fractions, this study focused only on the 0.5 inch (1.3 cm) size RCA. The first step is careful preparation of oven-dried samples (2.75 lb (1.25 kg)) by removing contaminants such as asphalt bricks, wood, and metal. The RCA samples are then placed in containers of appropriate size (1 L in this case) and subsequently filled with a prepared 3% sodium chloride (NaCl) solution to soak all the aggregate particles. The containers are then sealed and kept at room temperature for 24 hours. Afterwards, the solution is removed by inverting the containers over a screen smaller than 5 mm mesh. The containers are then sealed and placed in a 0°F (-18°C) freezer for 16 hours, which is the freeze cycle stage. The thaw cycle is initiated by removing the containers from the freezer and leaving them at room temperature for 8 hours. These cycles are repeated five times. After five freeze-thaw cycles, the aggregate is washed by filling the container with tap water and draining it by inverting it over a No. 4 mesh for five seconds. This process is repeated five times to ensure that the RCA particles are thoroughly washed. The sample is then dried in an oven at 110° C. for 24 hours. Finally, the oven-dried RCA sample is sieved using an appropriate sieve (0.5 inch (1.3 cm) in this case) and the mass loss is recorded.

[0053] Environmental Testing Laboratory batch leaching tests Laboratory batch leaching tests were conducted on untreated (original) and carbon dioxide treated samples to evaluate the effect of carbon dioxide treatment on the environmental profile of RCA sample 240. For this purpose, 10 lb. (4.54 kg) RCA sample 240 (1 inch (2.5 cm) graded and sorted similar to field-scale treatment) was submerged in 1 gallon (3.79 L) of distilled water 304 in a plastic bucket 300 (5 gallon (18.9 L) capacity) with a closed door 308 as shown in Figure 3. Leachate samples were then collected from the bucket 300 after 1, 2, 4, 7, 14 and 21 days of time. The pH value and total elemental concentration of the leachate samples were measured using a pH meter (Accumet AB15) and an ICP-MS (Inductively Coupled Plasma Mass Spectroscopy) device, respectively. The test procedure was modified from the Ohio DOT 2002 report.

[0054] Concrete mix with carbon dioxide treated RCA Concrete Mixing Capacity 3 cubic feet (ft 3 , 0.0849m 3 The concrete was mixed using a 1.5m2 drum mixer in compliance with the procedure described in ASTM C192 (Standard Practice for Preparing and Curing Test Specimens in the Laboratory). First, the coarse aggregate was mixed with approximately half the mix water containing AEA (air entraining agent) for 30 seconds. The sand and gravel, cement and remaining water were then added and mixed for 3 minutes, followed by a 3 minute rest and an additional 2 minutes of mixing. If workability adjustment was required, WR (water reducing agent) was added and the concrete was mixed for an additional 3 minutes. During the performance evaluation phase, if the WR addition was known for a particular mix, it was added with half the water for a second time. Prior to mixing, the aggregate was saturated and 1.3 ft2 of water was added. 3 (0.0368m 3 The amount of water was adjusted according to the moisture state of the aggregate before measuring for each mix, which was sized at 100°C.

[0055] Tables 5 and 6 show the mix designs and mix proportions for the mixtures in the study, where pcy is pounds per cubic yard and cwt is hundredweight or 100 pounds (45 kg). Fluid ounces per 100 pounds is therefore abbreviated as fl oz / cwt. The identification of the mixtures is based on three parameters: treatment pressure 404 (T for treated and U for untreated), fraction of RCA or NA (natural aggregate) 408 and river sand (RS) 412. For example, T5_RCA30-RS70 represents a mixture of RCA treated at 5 psig (34.5 kPa), fraction of RCA 30 and RS 70 (Figure 4). It should be noted that the mix designs for all RCA mixtures are the same since the specific gravity of RCA before and after carbon dioxide treatment is almost the same. Due to the lower specific gravity of RCA (compared to NA), a lower amount of coarse aggregate was used in the RCA mixture.

[0056] [Table 5]

[0057] [Table 6]

[0058] Results: Mesoscale carbon dioxide treatment Various carbon dioxide treatment conditions were applied to evaluate the effect of each variable on the carbon dioxide treatment procedure and the RCA mechanical and environmental properties, and the optimal variable ranges were finally found based on the resulting mechanical, environmental and cost analysis. The recorded parameters of all 35 individual mesoscale carbon dioxide treatments at various conditions are listed in Table 7.

[0059] [Table 7]

[0060] Physical and Mechanical Testing Specific Gravity and Absorption The specific gravity and absorbency of the untreated and carbon dioxide treated RCA samples at all treatment conditions according to ASTM C127 standard are listed in Table 8. Pressure is expressed in pounds per square inch gauge (psig). The results indicated that the specific gravity and absorbency of the RCA samples did not change significantly after carbon dioxide treatment at various treatment conditions.

[0061] [Table 8]

[0062] Aggregate Crushing Value (ACV) The ACV index of untreated and carbon dioxide treated RCA samples under different treatment conditions was measured based on the modified BS 110-812 standard. Figure 5 shows all measured ACV indexes combined for all treatment conditions. The results suggest that the ACV index decreases in the CO2 treated RCA samples under all treatment conditions. Among all the results, the ACV values ​​for SPB10 and SPB20 also show relatively lower values ​​and longer treatment times, which are mainly related to the higher contact surface between the RCA samples and carbon dioxide in the basket.

[0063] LA wear The mass loss of untreated and carbon dioxide treated RCA samples after LA abrasion test was measured using ASTM C131 standard. Figures 6A, 6B and 7 show such mass loss of RCA samples treated for SPB10 and 20 and CPB20 conditions, respectively. It is noted that the LA abrasion mass loss of limestone aggregate is about 26.8%. The results clearly indicate that the effect of carbonation treatment of RCA on mass loss is reduced.

[0064] Freeze and Thaw (FT) Resistance The mass loss of untreated and carbon dioxide treated RCA samples after freeze-thaw (FT) resistance test was measured based on CSA A23.2-24A standard. Figures 8A, 8B and 9 show such mass loss of RCA samples treated with SPB10 and 20 and CPB20 treatment conditions, respectively, for various CO2 pressures. The dashed line depicts the FT mass loss of limestone aggregate (2.63%). A clear trend of mass loss reduction is shown in the results when higher treatment pressures are applied.

[0065] Chemical and Environmental Testing As environmental tests, phenolphthalein pH indicator test and batch leaching test were conducted on untreated and carbon dioxide treated RCA samples. These tests aimed to evaluate the environmental remediation effect of CO2 treatment on RCA specimens under different conditions. The following sections present the phenolphthalein test, leachate pH and leachate ion concentration results, respectively.

[0066] pH of RCA (phenolphthalein test) treated with carbon dioxide The phenolphthalein test is a quick and easy method to roughly evaluate the acidity or basic condition of the surface and cross-section of RCA specimens. In this method, six RCA specimens were randomly selected, then phenolphthalein solution was dropped onto the surface of three specimens, a hammer was used to break the other three specimens, and phenolphthalein was dropped onto the freshly cut surfaces to assess the penetration depth of the carbon dioxide treatment.

[0067] Leachate: pH Six RCA leachate samples were collected after 1, 2, 4, 7, 14 and 21 days of time for each treatment condition. All water samples were alkaline (basic) and showed a trend of increasing pH over time, but the original (untreated) sample had the highest pH for a given time and treatment pressure. Based on the National Secondary Drinking Water Regulations (NSDWR), the standard pH value for drinking water is 6.5 to 8.5.

[0068] Leachate: Heavy metals Total elemental concentrations of RCA leachate samples from days 1 to 21 were measured using ICP-MS analytical technique. The concentrations of heavy metals in leachate from untreated and carbon dioxide treated samples under various conditions from days 1 to 21 were all well below the EPA maximum contaminant levels (MCLs) for drinking water.

[0069] CO 2 Performance of concrete treated with RCA Ready Mix Concrete Testing (1) Slump test Concrete slump was measured according to ASTM C143 (Standard Test Method for Slump of Hydraulic Cement Concrete) to measure the viscosity of the concrete. The test was performed immediately after the concrete mix was completed.

[0070] (2) Air content test The air content of the mixture was measured and determined according to ASTM C138 (Standard Test Method for Density (Unit Weight), Yield and Air Content (Gravimetric) of Concrete).

[0071] Table 9 summarizes the fresh concrete properties of the different concrete mixtures. The results revealed that all mixtures exhibited comparable properties regardless of the use of natural aggregates or treated / untreated RCA. The mixtures also exhibited reasonable workability and air content that met Nebraska Department of Transportation specifications. Unit weights are expressed in Table 9 as pounds per cubic foot (pcf).

[0072] [Table 9]

[0073] Hardened Concrete Test 1) Compressive strength Three 4 in. x 8 in. (10 cm x 20 cm) cylinders of each mixture were tested for compressive strength according to ASTM C39 (Standard Test Method for Compressive Strength of Cylindrical Concrete Specimens) at 28 days of maturity. All specimens were mechanically edge ground prior to each test. A compactor with a capacity of 400 kips (1,779 kN) was used.

[0074] Figure 10 demonstrates the compressive strength of the different mixtures. The results showed that all mixtures had a minimum compressive strength for pavement concrete applications of 3500 psi (24 MPa) at 28 days. The use of RCA results in a slight reduction in compressive strength. However, a clear trend of increasing compressive strength with increasing CO2 treatment pressure was observed, with the treatment pressures of 20 psig, 40 psig, and 60 psig (138 kPa, 276 kPa, and 414 kPa, respectively) used in this study resulting in compressive strengths equivalent to the reference mixture with added natural aggregate.

[0075] 2) Flexural strength (modulus of rupture) One 6 in. x 6 in. x 20 in. (15 cm x 15 cm x 51 cm) beam per mix was tested for modulus of rupture at 28 days according to ASTM C78 (Standard Test Method for Flexural Strength of Concrete (Using a Simple Beam with Three-Point Load)). A flexural tester with a capacity of 30 kips (133 kN) was used.

[0076] Figure 11 demonstrates the flexural strength (modulus of rupture) of the different mixtures. The results showed that all mixtures except the mixture with untreated RCA had a minimum modulus of rupture for pavement concrete applications of 600 psi (4 MPa) at 28 days. Similar to the results from the compressive strength tests, the use of RCA results in a slight reduction in compressive strength. However, a clear trend of increased flexural strength with increasing CO2 treatment pressure was observed, with the 40 psig (276 kPa) and 60 psig (414 kPa) treatment pressures used in this study resulting in flexural strengths equivalent to the reference mixture with natural aggregate.

[0077] 3) Static elastic modulus and Poisson's ratio test Elastic modulus tests were performed according to ASTM C469 (Standard Test Method for Static Elastic Modulus and Poisson's Ratio of Concrete in Compression) at 28 days. A frame with two dial gauges was used to monitor the axial and radial deformation. Each test was recorded and later used to construct a graph and calculate the properties accordingly.

[0078] Figure 12 demonstrates the elastic modulus and Poisson's ratio of the different mixes. The results showed that the use of RCA resulted in a slight reduction in the elastic modulus and Poisson's ratio. It is noteworthy that the properties do not have a significant impact on the design of the concrete. Unlike the compressive and flexural strengths, no clear trend of the effect of the CO2 treatment was observed.

[0079] 4) Surface and bulk resistivity One 4" x 8" (10 cm x 20 cm) cylindrical specimen was randomly selected from each mixture to be tested for surface and bulk resistivity using a Proceq Resipod test device per AASHTO TP95 (Standard Test Method for Surface Resistivity Indication of Concrete's Ability to Resist Chloride Ion Penetration) at 28 days. The Resipod works on the principle of the Wenner probe to measure the electrical resistivity of concrete. Specimens were fully saturated prior to testing. Current is applied through the outer probe while the inner probe measures the voltage.

[0080] Figure 13 demonstrates the surface and bulk resistivity of all mixtures. The use of RCA resulted in a slight reduction in surface and bulk resistivity, with the untreated RCA mixture exhibiting the lowest resistivity. However, a clear trend of increasing surface and bulk resistivity with increasing CO2 treatment pressure was observed, with the treatment pressures of 20 psig, 40 psig, and 60 psig (138 kPa, 276 kPa, and 414 kPa, respectively) used in this study resulting in surface and bulk resistivities equivalent to the reference mixture with added natural aggregate.

[0081] Analysis and Observations A detailed analysis based on the experimental data during the carbon dioxide treatment and subsequent mechanically and environmentally relevant laboratory tests on the carbon dioxide treated samples is presented in this specification. In the following sections, the treatment and laboratory results are analyzed based on the carbon dioxide mass consumption calculations, ongoing statistical analysis, cost analysis and carbon dioxide footprint.

[0082] carbon dioxide mass consumption The carbon dioxide pressure drop data individually may not be a comprehensive indicator of carbon dioxide gas consumption. Temperature and RCA volume may be major factors that must be taken into account when considering gas consumption. Therefore, carbon dioxide mass consumption was calculated to evaluate the amount and rate of carbon dioxide gas consumption during treatment in different treatment conditions, and then normalized by the initial RCA mass in each treatment condition. Carbon dioxide mass consumption may be one of the main indicators to quantify the intensity and magnitude of carbon dioxide treatment. In this regard, the density of carbon dioxide at the beginning of the test was calculated using the Penn and Robinson equation of state based on the initial carbon dioxide pressure and temperature inside the treatment (Equations 6-12). The initial mass of carbon dioxide in the chamber was then calculated by multiplying the carbon dioxide density by its volume, for which the volume in the chamber and the RCA volume were used to obtain the initial CO2 volume. Similarly, the mass of carbon dioxide at any time after the treatment was started was calculated using the same procedure. The carbon dioxide mass difference between the initial (t_0) and the time after the test was started (t_1-t_n) may represent the carbon dioxide mass consumption during the RCA treatment. The initial volume of the RCA sample in the chamber may not be the same in all mid-scale and lab-scale process tests. Therefore, the carbon dioxide gas consumption is normalized by the initial mass of the RCA in the chamber. In this way, the amount and rate of carbon dioxide gas consumption in all process conditions can be easily compared. In this section, carbon dioxide consumption graphs related to various mid-scale and lab-scale process conditions are presented.

[0083]

number

[0084]

number

[0085]

number

[0086]

number

[0087]

number

[0088]

number

[0089]

number

[0090] In the formula, P is the chamber pressure [Pa], and R is the universal gas constant = 8.3145 [J.mol -1 .k -1 ], T is the chamber temperature [K], and T r is the temperature (=T / T crit ), α is the gravitational parameter, and Z is the compressibility factor [-]. For pure carbon dioxide gas, p crit =73.8[bar], T crit =304.2[K], m=0.6877, n=0.3813, ρ is CO2 density [kg / m 3 ] and M is the molar mass of CO2 = 0.04401 [kg / mol].

[0091] Medium-scale carbon dioxide processing Various processing conditions were applied using prototypes to evaluate the effect of each parameter on the physical / mechanical properties and carbon dioxide consumption of RCA samples. Figures 14A, 14B, and 15 show the normalized carbon dioxide gas consumption in SPB10, SPB20, and SPD20 processing conditions, respectively. The exact amount of carbon dioxide mass consumption for the processing condition with continuous carbon dioxide pressure supply (CPB20) cannot be calculated precisely due to the continuous supply of carbon dioxide to the chamber. However, based on the calculated results for the SPB condition, the carbon dioxide consumption for the CPB20 condition was roughly estimated.

[0092] The carbon dioxide mass consumption results for different treatment conditions show greater gas consumption in the order of SPB10, SPB20 and SPD20. It may be interpreted that the initial volume of carbon dioxide in the chamber and the contact area between the RCA sample and carbon dioxide play an important role in the gas consumption during treatment. In the condition SPB10 with a lower volume of RCA and a higher amount of carbon dioxide gas, the carbon dioxide can be easily absorbed by the RCA, so faster carbonation can occur (Figures 14A and 14B). On the other hand, besides the carbon dioxide / RCA volume, the arrangement of the RCA sample in the chamber may play an important role during the carbon dioxide treatment and carbon dioxide mass consumption. The gas consumption is lower in the condition with a simple loose loading arrangement (Figure 15), probably due to the limited contact area between the RCA sample and carbon dioxide in the chamber.

[0093] Since the carbon dioxide / RCA volume ratios for conditions SPB20 and CPB20 are similar, the amount of carbon dioxide consumption in CPB20 was roughly calculated based on the SPB20 data, as shown in Table 10.

[0094] [Table 10]

[0095] Lab-scale carbon dioxide treatment Carbon dioxide mass consumption for various processing conditions using two sizes of chambers was also evaluated using the Penn and Robinson equation of state (EOS).

[0096] Chamber capacity 10L Carbon dioxide mass consumption for the smaller lab-scale chambers was calculated using similar calculations. The initialization method was the only variable examined using the smaller chambers. Figures 16A, 16B, 17A and 17B show the carbon dioxide mass consumption during carbon dioxide treatment of the RCA for different initial set pressures with initial CO2 vacuum and CO2 purge, respectively. Figures 16A and 16B show the carbon dioxide mass consumption and normalized by RCA mass for all process pressures using the CO2 vacuum initialization method. Figures 17A and 17B show the carbon dioxide mass consumption and normalized by RCA mass for all process pressures using the CO2 purge initialization method.

[0097] The carbon dioxide consumption results are relatively similar for both the CO2 vacuum and CO2 purge initialization methods. Therefore, the CO2 purge method was selected as the initialization method for the 30 L chamber.

[0098] 30L capacity chamber Various treatment conditions were evaluated at laboratory scale using a 30 L volume chamber (see Table 3). Carbon dioxide mass consumption graphs for each treatment variable are presented herein to easily assess the effectiveness of each treatment condition on carbon dioxide mass consumption.

[0099] 18A and 18B show the carbon dioxide mass consumption and normalized by RCA mass for all treatment conditions with different average RH during treatment. The solid line shows the increase in carbon dioxide mass consumption by increasing RH from 1.88% up to 55.1%, and then the long open dashed line shows the decrease in carbon dioxide mass consumption by increasing RH above 55.1% up to a maximum value of 76.7%. The chamber did not increase the average RH above 76.7% at normal laboratory temperature, which was the maximum RH achieved.

[0100] The results may show that maximum carbon dioxide consumption may occur at a humidity of 50±5° C. These results confirm the optimal RH range for the carbonation process of RCA using carbon dioxide.

[0101] 19A and 19B show carbon dioxide mass consumption and normalized by RCA mass for similar process conditions (i.e., no silica gel and initial pressure of 40 psig (276 kPa)) at different process temperatures. The solid line shows carbon dioxide mass consumption at typical laboratory temperatures (21° C. to 25° C.), while the open dashed line and long open dashed line represent carbon dioxide mass consumption at a cooler temperature of about 3° C.

[0102] Temperature may be another major factor influencing chemical reactions and therefore carbonation. In general geochemistry, the higher the temperature, the faster the chemical reactions. Results may show that carbonation and carbon dioxide consumption may be limited at low temperatures (e.g. 3°C).

[0103] Despite the similar test conditions (i.e., no silica gel) for all treatments presented in Figures 19A and 19B, the average RH is different during the treatment inside the control room (at 3±0.5°C) due to different dew points at different temperatures. In Figures 20A and 20B, the continuous solid lines show the carbon dioxide mass consumption for the treatments at laboratory temperature and using 150g SG in the middle layer, and the dotted and dashed lines represent the carbon dioxide mass consumption for the treatments in the control room at a constant temperature of 3±0.5°C and without silica gel (No SG). Thus, the carbon dioxide consumption results of the treatments with similar average RH are presented in Figures 20A and 20B. This comparison confirms that the rate of carbon dioxide consumption is still reasonable; thus, the carbonation of RCA is slower at low temperatures.

[0104] The carbon dioxide consumption of the treatments with different sample preconditioning is presented in Figures 21A and 21B (W: washing and N: no washing of RCA; C: RCA placed in a control room with RH = 50 ± 2% and = 22 ± 1 °C for 24 h before treatment; L: RCA placed in a laboratory room with RH = 58 ± 2% and T = 22 ± 1 °C; O: RCA dried in an oven at 105 °C for 24 h before treatment). The lowest carbon dioxide consumption was obtained for the oven-dried RCA sample. Since the carbonation reaction is known to require the presence of moisture in which CO2 can dissolve, the carbonation of RCA, and therefore the carbon dioxide consumption, is limited when the RCA is oven-dried. Comparing the conditions with washing and drying in a control room (WC) and washing and drying in the laboratory (WL), the carbon dioxide consumption is lower in the WL condition, which may be due to the higher initial moisture content and average RH. Washing and drying in the control room (WC) and washing and not drying in the laboratory (NL) showed similar carbon dioxide consumption, probably due to similar average RH during the treatment and cleaned samples. Therefore, washing does not seem to affect the carbon dioxide penetration and consumption rate.

[0105] 22, one or more aspects of the present disclosure can provide a method of processing recycled concrete aggregate (RCA). The method can include loading the RCA into a chamber configured to form an airtight seal; hermetically sealing the chamber; purging the chamber of non-carbon dioxide gas; pressurizing the chamber with carbon dioxide gas; and monitoring and maintaining temperature and humidity within the chamber until predetermined conditions are met.

[0106] In one or more embodiments, the method may further include at least one of the group consisting of cleaning the RCA by immersing the RCA in water at least once prior to loading the RCA; drying the RCA prior to loading the RCA; and stabilizing the temperature of the RCA prior to loading the RCA. Drying the RCA may include blowing air over the RCA.

[0107] In one or more embodiments, purging may include pressurizing the chamber with carbon dioxide at a low pressure of (2-3 psig (13.8-20.7 kPa) one or more times, followed by releasing the pressure by opening a relief valve to the exterior of the vessel or venting the chamber. Pressurizing may include injecting an initial volume of carbon dioxide gas sufficient to raise the pressure in the chamber to a predetermined level. Additionally, additional carbon dioxide gas may be injected into the chamber to maintain the pressure in the chamber at the predetermined level. In one or more embodiments, the carbon dioxide gas may be at least 99% pure.

[0108] In one or more embodiments, the predetermined condition may be a treatment time or a pressure within a chamber.

[0109] In one or more embodiments, the pressure in the chamber may be maintained at a gauge pressure of 20-60 psig (138-414 kPa), the treatment time may be 4-12 hours, loading the RCA may include filling 10%-20% of the volume of the chamber with the RCA, the humidity in the chamber may be maintained at 40%-60%, and the temperature in the chamber may be maintained at 20°C-30°C.

[0110] In one or more embodiments, the processed recycled concrete aggregate (RCA) may have been processed according to all or some of the methods described above.

[0111] One or more of the above methods may be carried out using the chambers disclosed herein.

[0112] One or more aspects of the invention may provide a method of optimizing the carbonation of recycled concrete aggregate (RCA). The method may include performing multiple experiments on the carbonation of RCA, varying input parameters between successive experiments. Varying the input parameters may include varying sample preconditioning to either include or exclude washing and drying the RCA prior to placing it in the carbonation chamber; varying the volume of the carbonation chamber from 10 L to 2×10 L; 4L; varying the percentage of the volume of the carbonation chamber occupied by the RCA from 1% to 50%; varying the temperature of the carbonation chamber from 0° C. to 80° C.; varying the humidity of the carbonation chamber from 10% to 75%; varying the gauge pressure of carbon dioxide gas in the carbonation chamber from 1 psig to 100 psig (6.9 kPa to 690 kPa); varying initial carbon dioxide pressurization or continuous carbon dioxide pressurization; varying purging the carbonation chamber by applying a vacuum or by at least one cycle of pressurization with carbon dioxide gas followed by depressurization; varying the distribution of RCA in the carbonation chamber and in the plurality of baskets, including simple loose loading; varying the duration of carbonation from 1 hour to 72 hours; monitoring a plurality of parameters as a function of time during each experiment for the RCA during treatment, including at least one parameter selected from the group consisting of temperature of the carbonation chamber, humidity of the carbonation chamber, gauge pressure of carbon dioxide gas in the carbonation chamber, ratio of carbon dioxide mass to RCA mass, and carbon dioxide mass consumption.

[0113] The method may further include performing a number of experiments and measurements (on the RCA) after the carbonation process. These experiments and measurements may include specific gravity; absorbency; aggregate crushing value; Los Angeles abrasion; freeze-thaw resistance; phenolphthalein testing; and laboratory batch leaching tests. The laboratory batch leaching tests may include measuring pH and concentrations of heavy metals, including at least one of the group consisting of Pb-208, Se-78; Cd-112; Cr-52, and As-75.

[0114] The method may further include measuring properties of the plurality of concretes including the plurality of carbonated RCA blends, which may include compressive strength, modulus of rupture, modulus of elasticity, surface resistivity, and bulk resistivity.

[0115] The method may further include acquiring data before, during and / or after each carbonation treatment; analyzing the acquired data using at least one of the group consisting of univariate regression, multivariate regression, principal component analysis and singular value decomposition to determine optimal ranges and / or optimal values ​​of a plurality of input parameters for carbonating the RCA for at least one property of the RCA after carbonation.

[0116] All references cited in this specification, including publications, patent applications, and patents, are hereby incorporated by reference to the same extent as if each reference was individually and specifically indicated to be incorporated by reference and was set forth in its entirety herein.

[0117] In this specification (especially in the claims), the use of the terms "a," "an," "the," and "at least one," and similar referents, should be construed to cover both the singular and the plural, unless otherwise indicated herein or clearly contradicted by context. The term "at least one," followed by a list of one or more items (e.g., "at least one of A and B"), should be construed to mean one item (A or B) selected from the listed items, or any combination of two or more of the listed items (A and B), unless otherwise indicated herein or clearly contradicted by context. The terms "including," "having," and "containing" should be construed as open-ended terms (i.e., meaning "including but not limited to"), unless otherwise noted. The recitation of ranges of values ​​herein is merely intended to serve as a shorthand method of individually referring to each separate value falling within the range, unless otherwise indicated herein, and each separate value is incorporated herein as if it were individually recited herein. All methods described in the specification can be performed in any suitable order, unless otherwise indicated herein or clearly contradicted by context. The use of any and all examples or exemplary language (e.g., "such as") provided herein is intended only to better elucidate the invention, and does not impose limitations on the scope of the invention unless otherwise claimed. No language in the specification should be construed as indicating any non-claimed element as essential to the practice of the invention.

[0118] Preferred embodiments of the invention, including the best mode known to the inventors for carrying out the invention, are described in the specification. Variations of those preferred embodiments may become apparent to those skilled in the art upon reading the foregoing description. The inventors expect that those skilled in the art will employ such variations as appropriate, and the inventors intend for the invention to be practiced otherwise than as specifically described herein. Accordingly, the present invention includes all modifications and equivalents of the subject matter recited in the claims as permitted by applicable law. Moreover, any combination of the above-described elements in all possible variations thereof is encompassed by the present invention unless otherwise indicated herein or otherwise clearly contradicted by context.

Claims

1. 1. A method for treating recycled concrete aggregate (RCA), comprising: constructing a chamber configured to form an airtight seal; loading said RCA into said chamber; hermetically sealing said chamber; pressurizing said chamber with carbon dioxide gas; monitoring the pressure and humidity within the chamber; and Controlling the pressure and humidity until a predetermined condition is met. A method comprising:

2. The method of claim 1 , wherein controlling the pressure and humidity comprises setting at least one of the pressure and humidity to a fixed or initial value and controlling the other until a predetermined condition is met.

3. The method of claim 1 , wherein pressurizing comprises injecting a sufficient volume of carbon dioxide gas to raise the pressure in the chamber to a predetermined level.

4. 4. The method of claim 3, further comprising injecting additional carbon dioxide gas to maintain the pressure in the chamber at the predetermined level.

5. 10. The method of claim 1, wherein the carbon dioxide has a purity of less than 99%.

6. 10. The method of claim 1, wherein the carbon dioxide gas has a purity of at least 99%.

7. The method of claim 1 , wherein the predetermined condition is a treatment time or a pressure in the chamber.

8. maintaining a pressure in said chamber at 20 to 80 pounds per square inch gauge; The treatment time is 1 to 12 hours, loading the RCA into the chamber includes providing an airflow around the RCA; maintaining the humidity in the chamber at between 40% and 60%; Maintaining the temperature in the chamber at 20°C to 30°C; The method of claim 1.

9. Into said chamber: At least one pressure sensor; and at least one humidity / temperature sensor; at least one dehumidifier; at least one system configured to collect water from the at least one dehumidifier; At least one blower Prepare; providing at least one gas inlet valve and at least one gas outlet valve operably connected to said chamber; The method of claim 1 further comprising:

10. 1. A processed recycled concrete aggregate (RCA), comprising: The RCA loaded into the chamber and hermetically sealed; and treating said RCA by exposing it to a carbon dioxide enriched atmosphere at elevated pressure in said chamber, wherein the temperature and humidity of said atmosphere are monitored and controlled until predetermined conditions are met; wherein treating the RCA changes the proportions of constituent minerals in the RCA, increasing the proportion of calcium carbonate and silica as a result of the reaction of calcium hydroxide, calcium silicate hydrate and carbon dioxide.

2. A processed recycled concrete aggregate (RCA) comprising:

11. maintaining the pressure in the chamber at 20 to 80 pounds per square inch gauge; The treatment time is 1 to 12 hours, loading the RCA into the chamber includes providing an airflow around the RCA; The humidity in the chamber is maintained at 40% to 60%; The temperature in the chamber is maintained at 20°C to 30°C.

11. The treated recycled concrete aggregate (RCA) of claim 10.

12. 1. A method for carbonating recycled concrete aggregate (RCA), comprising: constructing a chamber configured to form an airtight seal; loading said RCA into said chamber; hermetically sealing said chamber; pressurizing said chamber with carbon dioxide gas; monitoring the pressure, temperature and humidity within the chamber; and Controlling the pressure, temperature and humidity until predetermined conditions are met. A method comprising:

13. The method of claim 12 , further comprising preconditioning the RCA prior to placing the RCA in the chamber by cleaning and / or drying the RCA.

14. 13. The method of claim 12, further comprising monitoring the pressure in the chamber and maintaining the pressure in the chamber by injecting additional carbon dioxide gas into the chamber.

15. 13. The method of claim 12, further comprising purging the chamber by applying a vacuum or by at least one cycle of pressurization with carbon dioxide gas followed by depressurization.

16. 13. A method for improving the mechanical and durability properties of Portland cement concrete (PCC), comprising treating recycled concrete aggregate (RCA) contained in said PCC with the method of claim 12.

17. 13. A method for improving the mechanical and durability properties of asphalt cement concrete (ACC), comprising treating recycled concrete aggregate (RCA) contained in the ACC with the method of claim 12.

18. 1. A system for processing recycled concrete aggregate (RCA), comprising: A chamber configured to form an airtight seal, the chamber having a volume between 10 L and 3×10 4 a chamber including a door configured to form an airtight seal at L; at least one dehumidifier disposed within the chamber and configured to maintain humidity within the chamber; at least one system disposed within the chamber and configured to collect water from the at least one dehumidifier; A CO 2 at least one blower configured to circulate the gas and moisture; at least one heating element; at least one pressure sensor disposed within the chamber and configured to measure pressure within the chamber; at least one humidity / temperature sensor disposed within the chamber and configured to measure humidity and temperature within the chamber; a supply of carbon dioxide gas operably connected to said chamber via an inlet valve; a blow-off valve disposed on the chamber and configured to allow gas to be exhausted from the chamber; Including, the system.